CLINICAL DEPRESSION: FORENSIC INTERPRETATION OF TWO CASES - Feodor Odzhakov; Diyana Belezhanska; Aleksandar Apostolov (Science & Research)

(untitled)
Introduction Clinical depression is one of the common mental disorders worldwide. In recent years, it has been established that more and more young adults have been diagnosed with this condition. Materials and Methods In the following study two separate cases of suicides by mechanical asphyxia from the Department of Forensic Medicine and Deontology at University hospital Alexandrovska – Sofia have been presented. Both of them are young males, found alone in their homes, with plastic bags around their heads. In both cases, a suicide note has been found at the scene. Results The autopsy finding in both cases has established relatively unspecific findings. The toxicology report of one of them has stated a concentration of 78 µg/mL pentobarbital in the blood sample and no other substances. The toxicology report of the other male has been clean. The cause of the death in both cases has been established as mechanical asphyxia from the plastic bags that have been found on their heads. Discussion In both cases presented the relatives and close friends of the deceased have stated that no indicators of social distancing have been noticed prior to the suicides and no previous attempts have been registered as well. Given the choice of method for committing the suicide and the lack of apparent reason for it, clinical depression must be considered in these cases. Conclusion The discussion for prevention of clinical depression should be active and attempts towards successful and in-time diagnosis and treatment must be made.